Series solution of typhoid fever model using differential transform method / Olumuyiwa James Peter ... [et al.] - Peter, Olumuyiwa James; Akinduko, Oluwaseun; Ishola, Christie; Afolabi, Ahmed; Ganiyu, Afees (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
This paper presents an analysis of PSIuIeTR type model, which are used to study the transmission dynamics of typhoid fever diseases in a population. Basic idea of typhoid fever disease transmission using compartmental modeling is discussed. Differential Transformation Method (DTM) is discussed in detail, which is used to compute the series solution of the non-linear system of differential equation governing the model equations. The validity of the (DTM) in solving the proposed model is established by classical fourth-order Runge-Kutta method which is implemented in Maple 18. Graphical results confirm that (DTM) is in good agreement with RK-4 and this produced correctly same behaviour of the model, thus validating the efficiency and accuracy of (DTM) in finding the series solution of an epidemic model.